Statistical Insights of the Effectiveness Using Serial Cartoon Pictures and Learning Motivation among Eighth Students’ Speaking Skills: English - Endah Agustiani; Tahrun; Mulyadi (Prodi Tadris Bahasa Inggris, 2024)
One of the important skills students need to be learned English is speaking skills because it is complex skills. In learning speaking skills students learn how to write, read, and listen at once indirectly which is important for language communication. But the problem arises when the students feel that English is difficult and the learning method that use are not enjoyable. This research aims to change students’ mindset about learning English and of course improve students’ speaking skills. Also, this research aims to see the effect of using Serial Cartoon Pictures and Learning Motivation on students’ speaking skills. This research was experimental. There are 56 students as samples who have been selected using a simple random sampling technique, half of whom taught using Serial Cartoon Pictures and guided with learning motivation and the rest as comparisons. A questionnaire and speaking test were used to collect the data. The result showed that Using Serial Cartoon Pictures as a media and learning motivation as a reference for guidance can improve students’ speaking skills; as shown by the calculation analysis data result of 2 rater, most students reached more than half the maximum score of speaking rubric. Also, statistical result revealed that the calculation of p-output was lower than 0.05.